Meta Analysis: The Effect of Age and Gender on Face Mask Use during COVID-19 Pandemic - Indah Adhitama Chrisnanda; Hanung Prasetya; Bhisma Murti (Masters Program in Public Health, 2022)
Background: Coronavirus disease 2019 (COVID-19) is a world health problem in early 2020. The first case of COVID-19 was found in Wuhan China, the use of masks is intended to control the transmission of the virus to others and as a preventive measure, namely by providing protection to users who do not infected with viral exposure. The purpose of this study was to estimate the extent of adherence to wearing masks in the elderly and women through a meta-analysis of the primary study which was carried out by the previous authors.Subjects and Method: This study was a meta-analysis with the following PICO, PICO. Population: general population, intervention: age (older > 46) and gender (female), comparison: age (young 12 - 45 years) and gender (male), outcome: use of masks. The articles used in this study were obtained from three databases, namely Google Scholar, Pubmed, and Science Direct. With keywords such as: “mask and COVID-19 transmission”, “mask or COVID-19 transmission”. The articles included are full-text English with an observational study design from 2020 to 2022. Article selection was carried out using PRISMA flow diagram. Articles were analyzed using the Review Manager 5.3 application.Results: A total of 9 case studies from Europe, America and Asia were selected for systematic review and meta-analysis. The results showed that people over 46 years of age were 1.54 times more likely to use a mask than those under 45 years old (aOR= 1.54; 95% CI= 0.83 to 2.85; p= 0.170) and women were 1.12 times more likely to use a mask than men (aOR= 1.12; 95% CI= 0.78 to 1.61; p= 0.550).Conclusion: Older age and women are more likely to wear masks. Keywords: wearing mask, gender, age, COVID-19 Correspondence:Indah Adhitama Chrisnanda. Master Program in Public Health. Universitas Sebelas Maret, Jl. Ir. Sutami 36 A, Surakarta 57126, Central Java, Indonesia. Email: indahthama1919@gmail.com Mobile: 081216121662.